Robust aeronautical communications enabled by UAV operations and LEO satellites - Subasu, Stefan; Al-Rubaye, Saba; Tsourdos, Antonios (IEEE, 2025)
In the realm of modern aerospace communications, the integration of Unmanned Aerial Vehicles (UAVs) with Low Earth Orbit (LEO) satellite constellations can offer a transformative solution for enabling Beyond Visual Line of Sight (BVLOS) operations. Due to initial safety operation demand of UAV BVLOS communication new metrics, this paper proposes a new quality of service (QoS) framework for uplink communication between IRIDIUM satellite constellation and UAV. The objective is to benchmark key QoS metrics for UAVLEO communications using a Non-Terrestrial Network (NTN) narrowband (NB) channel. However, this study performs metrics such as latency and throughput across various elevation angles and environments. Different sample rates are evaluated to assess their impact on communication performance. Simulation analysis indicate that lower sample rates provide reduced latency and stable throughput suitable for telemetry, while higher sample rates increase throughput at the cost of higher latency. This study can be a road map for QoS metrics for optimizing satellite communication systems in UAV operations and demonstrates optimal communication for BVLOS missions in rural, suburban and underserved areas where ground infrastructure is limited. The findings are compared against current standards and regulatory benchmarks for validation.
Keywords: 4613 Theory Of Computation; 46 Information and Computing Sciences; 40 Engineering; Future Communication; NTN; UAV; QoS; LEO satellites; SatCom